Enzymatic and non-enzymatic comparison of two different industrial tomato (Solanum lycopersicum) varieties against drought stress - AYAN, ALP; ATAK, ÇİMEN; ÇELİK, ÖZGE (Springer, 233 Spring St, New York, Ny 10013 USA, 2017)
Background: The aim of this study is to compare the tolerance mechanisms of two industrial tomato varieties (X5671R and 5MX12956) under drought stress. 14 days-old tomato seedlings were subjected to 7 days-long drought stress by withholding irrigation. The effects of stress were determined by enzymatic and non-enzymatic parameters. The physiological damages were evaluated via lipid peroxidation ratio, total protein content, relative water content, chlorophyll content and proline accumulation. Enzymatic responses were determined by biochemical analysis and electrophoresis of SOD, APX, POX and CAT enzymes. Results: Relative water contents of X5671R and 5MX12956 varieties at 7th day of drought were decreased to 8.4 and 12.2%, respectively. Applied drought decreased all photosynthetic pigments of X5671R and 5MX12956 varieties during the treatment period significantly comparing to the Day 0 as the control. Total protein content, lipid peroxidation and proline accumulation presented increased values in both varieties in accordance with the increasing stress intensity. According to lipid peroxidation analysis, 5MX12956 tomato variety was found more drought sensitive than X5671R variety. Antioxidative enzyme activities showed increases in both varieties as a response to drought stress, although CAT and APX activities presented decrease on the 7th day of applied stress. 7 days long drought stress differentially altered POX, APX and SOD isozyme patterns. Same POX bands were observed in both varieties with different band intensities. Conclusions: However, main isozyme pattern differences were obtained for SOD and APX. APX1, Fe-SOD and Cu/Zn-SOD2 isozyme bands should be evaluated to define their main role in the tolerance mechanism of both tomato varieties.
Keywords: Solanum lycopersicum; Drought stress; Antioxidant enzyme activities; Isozyme pattern; Water-Stress; Oxidative Stress; Lipid-Peroxidation; Ascorbate Peroxidase; Antioxidant Responses; Superoxide-Dismutase; H2O2 Accumulation; Plant-Responses; Proline Content; Defense System